Output, Capital, and Labor in the Short, and Long-Run - Daniel Levy (Southern Economic Journal, 1994)
Using a new series of capital stock and frequency domain analysis, this paper provides new empirical evidence on the relative importance of capital and labor in the determination of output in the short and long-run. Contrary to the common practice in the traditional growth accounting literature of assigning weights of 0.3 and 0.7 to capital and labor inputs respectively, the evidence presented here suggests that capital is a far more important factor than labor for determination of output at and near the zero frequency band. Furthermore, I show that the zero-frequency labor elasticity of output may well be close to zero, or even zero. Additional findings reported here support the traditional accelerator model of investment as a good description of the long-run investment process.
Keywords: O47; E22; E24; E32; 330; Growth Accounting; Capital Investment; Output Fluctuation; Employment; Spectrum and Cross-Spectrum; Coherence; Phase Shift; Gain; Zero-Frequency; Capital and Labor Elasticity of Output; Short-Run; Long-Run; Capital's and Labor's Share in Output; Accelerator Model of Investment